Curable resin composition, curable film, and laminated film
By adding rubber, epoxy crosslinking components, ester hardening agents and hardening accelerators to the hardening resin composition, the problem of insufficient low dielectric characteristics in the high frequency region of existing hardening products is solved, and printing and distribution is realized The excellent low dielectric characteristics and continuity of the wire plate improve signal transmission performance.
Patent Information
- Application Number
- CN202380034332.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-07-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing hardened substances have insufficient low dielectric characteristics in high-frequency regions, making it difficult to meet the requirements of printed wiring boards for low dielectric constant and low dielectric loss tangent.
A hardening resin composition is adopted, including a rubber component, a crosslinking component with an epoxy group, an ester-based hardening agent and a hardening accelerator. By optimizing the proportion and type of these components, it can form excellent low dielectric properties and adhesion. hardener.
It realizes hardened substances with excellent low dielectric characteristics in high-frequency regions, and improves the signal transmission performance and circuit protection effect of the printed wiring board.
Smart Images

Figure BDA0005085892600000061 
Figure BDA0005085892600000161
Abstract
Description
Technical Field
[0001] The present disclosure relates to a curable resin composition, a curable film, and a laminated film. Background Art
[0002] In recent years, along with the high speed of the transmission signal in the printed wiring board, the high frequency of the signal is constantly developed.Accompanied by this, about the printed wiring board, the requirement of the low dielectric properties (low dielectric constant, low dielectric loss tangent) in the high frequency region is improved.In addition, about the protective layer (covering layer) coated on the circuit of the printed wiring board, the interlayer adhesive in the multilayer printed wiring board, etc., except requiring the adhesion with base material etc., also requiring to have low dielectric properties.As the resin composition that can obtain the hardener with low dielectric properties, for example, in patent documentation 1, an adhesive composition comprising styrene elastomer is proposed.
[0003] [Prior art literature]
[0004] [Patent Document]
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-150543 Summary of the invention
[0006] [Problems to be solved by the invention]
[0007] However, the cured product formed from the adhesive composition described in Patent Document 1 does not have sufficient low dielectric properties in the high frequency region, and there is room for further improvement.
[0008] The present disclosure has been made in view of the above circumstances, and an object thereof is to provide a curable resin composition capable of forming a cured product having good adhesion to an adherend and excellent low dielectric properties in a high frequency region, and a curable film and a laminated film using the same.
[0009] [Technical means to solve the problem]
[0010] In order to solve the above problems, the present disclosure provides the following curable resin composition, curable film, and laminated film.
[0011] [1] A curable resin composition comprising (A) a rubber component, (B) a crosslinking component having an epoxy group, (C) an ester-based curing agent, and (D) a curing accelerator.
[0012] [2] The curable resin composition according to [1], which is used to form a protective layer for covering a circuit.
[0013] [3] The curable resin composition according to [1] or [2], wherein the weight average molecular weight of the crosslinking component (B) having an epoxy group is 200 to 1,000.
[0014] [4] The curable resin composition according to any one of [1] to [3], wherein the content of the (D) curing accelerator is 0.1 to 10 parts by mass based on 100 parts by mass of the total amount of the (A) rubber component, the (B) crosslinking component having an epoxy group, and the (C) ester curing agent.
[0015] [5] A curable film comprising the curable resin composition according to any one of [1] to [4].
[0016] [6] A laminated film comprising: a base film; and the curable film according to [5] above, which is provided on the base film.
[0017] [Effects of the Invention]
[0018] According to the present disclosure, a curable resin composition capable of forming a cured product having good adhesion to an adherend and excellent low dielectric properties in a high frequency range, and a curable film and a laminated film using the same can be provided. DETAILED DESCRIPTION
[0019] Hereinafter, several embodiments of the present disclosure will be described in detail, but the present disclosure is not limited to the following embodiments.
[0020] In this specification, the numerical range represented by "~" indicates a range that includes the numerical values recorded before and after "~" as the minimum and maximum values, respectively. In the numerical range described in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be replaced by the upper limit or lower limit of the numerical range of other stages. In addition, in the numerical range described in this specification, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment. In the case of the amount of each component in the composition mentioned in this specification, when there are multiple substances equivalent to each component in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition. The so-called "A or B" only needs to include any one of A and B, and can also include both. The so-called "solid content" refers to the non-volatile component after removing the volatile substances (water, solvent, etc.) in the resin composition. That is, the so-called "solid content" refers to the components other than the solvent that does not volatilize and remain in the drying of the resin composition described later, and also includes liquid, syrupy or waxy components at room temperature (25°C). In this specification, for example, "(meth)acrylic acid" means "acrylic acid" and its corresponding "methacrylic acid", and the same applies to other similar words.
[0021] [Curing resin composition]
[0022] The curable resin composition of the present embodiment contains (A) a rubber component, (B) a cross-linking component having an epoxy group, (C) an ester curing agent and (D) a curing accelerator. The curable resin composition may also contain (E) a filler as needed. The curable resin composition of the present embodiment can be used as a protective layer (covering layer) for coating the circuit in the printed wiring board, an interlayer adhesive in a multilayer printed wiring board, etc. By using the curable resin composition of the present embodiment, a cured product (protective layer and adhesive layer, etc.) having excellent adhesion to the adherend, such as the metal part of the printed wiring board, the substrate, etc., which constitutes the printed wiring board, and low dielectric properties in the high frequency region can be formed. In addition, the curable resin composition of the present embodiment contains (A) a rubber component, so the cured product can be retractable. Therefore, the curable resin composition of the present embodiment can be suitably used as a protective layer forming application and an interlayer adhesive for a flexible printed wiring board, for example. Below, each component that can be included in the curable resin composition is described.
[0023] <(A) Rubber component>
[0024] The (A) rubber component may include, for example, at least one rubber selected from the group consisting of acrylic rubber, isoprene rubber, butyl rubber, styrene butadiene rubber, butadiene rubber, styrene butylene styrene rubber, styrene ethylene propylene styrene rubber, styrene ethylene butylene styrene rubber, acrylonitrile butadiene rubber, silicone rubber, urethane rubber, chloroprene rubber, ethylene propylene rubber, fluororubber, vulcanized rubber, epichlorohydrin rubber, and chlorinated butyl rubber. From the perspective of reducing the influence on insulation reliability caused by moisture absorption, reducing the influence on connection reliability, and reducing damage to wiring, a rubber component with low gas permeability may also be used. From this perspective, the (A) rubber component may also include at least one selected from styrene butadiene rubber, butadiene rubber, styrene ethylene butylene styrene rubber, and butyl rubber. The (A) rubber component may also include styrene ethylene butylene styrene rubber.
[0025] Examples of commercially available products of acrylic rubber include “Nipol AR series” manufactured by ZEON Co., Ltd. and “KURARITY series” manufactured by Kuraray Co., Ltd.
[0026] Examples of commercially available isoprene rubbers include "Nipol IR series" manufactured by ZEON Co., Ltd. of Japan.
[0027] Examples of commercially available butadiene rubbers include "Nipol BR series" manufactured by ZEON Co., Ltd. of Japan.
[0028] Examples of commercially available products of acrylonitrile butadiene rubber include “NBR series” manufactured by ENEOS Materials Co., Ltd. (formerly “JSR NBR series” manufactured by JSR Corporation).
[0029] As a commercial item of silicone rubber, "KMP series" manufactured by Shin-Etsu Silicone Co., Ltd. is mentioned, for example.
[0030] Examples of commercially available products of ethylene propylene rubber include “EP series” manufactured by ENEOS Materials Co., Ltd. (formerly “JSR EP series” manufactured by JSR Co., Ltd.).
[0031] Examples of commercially available fluororubbers include “DAIEL series” manufactured by Daikin Co., Ltd., and the like.
[0032] Examples of commercially available products of epichlorohydrin rubber include "Hydrin series" manufactured by ZEON Co., Ltd. of Japan.
[0033] The (A) rubber component can also be produced by synthesis. For example, acrylic rubber can be obtained by reacting (meth)acrylic acid, (meth)acrylate, aromatic vinyl compound, cyanide vinyl compound, and the like.
[0034] (A) rubber component may also contain a rubber having a crosslinking group. By using a rubber having a crosslinking group, there is a tendency to easily improve the strength, heat resistance and adhesion of the hardened material. The crosslinking group can be any reactive group that can carry out a reaction that crosslinks the molecular chain of the rubber component (A). Examples thereof include: reactive groups, anhydride groups, amino groups, hydroxyl groups, epoxy groups and carboxyl groups possessed by the crosslinking component (B) described later.
[0035] The (A) rubber component may also include a rubber having at least one crosslinking group of an anhydride group or a carboxyl group. As an example of a rubber having an anhydride group, a rubber partially modified with maleic anhydride can be cited. A rubber partially modified with maleic anhydride is a polymer containing a constituent unit derived from maleic anhydride. The (A) rubber component may also include a rubber partially modified with maleic anhydride. As a commercially available product of a rubber partially modified with maleic anhydride, for example, there is a styrene elastomer "Tufprene 912" manufactured by Asahi Kasei Corporation.
[0036] The rubber partially modified with maleic anhydride may also be a hydrogenated styrene elastomer partially modified with maleic anhydride. Hydrogenated styrene elastomers may also be expected to have the effects of improved connection reliability, improved insulation reliability, and improved weather resistance. Hydrogenated styrene elastomers are elastomers obtained by addition reaction of hydrogen with unsaturated double bonds of a styrene elastomer having a soft segment containing unsaturated double bonds. Examples of commercially available products of hydrogenated styrene elastomers partially modified with maleic anhydride include "FG1901", "FG1924GT" of Kraton polymers Japan Co., Ltd., and "TufTech M1911", "TufTech M1913", and "TufTech M1943" of Asahi Kasei Co., Ltd. The hydrogenated styrene elastomer partially modified with maleic anhydride may also be a hydrogenated styrene ethylene butylene styrene elastomer partially modified with maleic anhydride.
[0037] From the viewpoint of coating properties and circuit embedding properties, the weight average molecular weight of the rubber component (A) may be 20,000 to 200,000, 30,000 to 150,000, or 50,000 to 125,000. The weight average molecular weight (Mw) herein refers to a standard polystyrene conversion value determined by gel permeation chromatography (GPC).
[0038] In the curable resin composition, the content of the rubber component (A) is preferably 60% to 95% by mass, more preferably 65% to 90% by mass, and further preferably 70% to 85% by mass, based on the total amount of the rubber component (A), the cross-linking component (B) and the ester curing agent (C). If the content of the rubber component (A) is 60% by mass or more, there is a tendency that the rubber component and the cross-linking component are fully mixed. If the content of the rubber component (A) is 95% by mass or less, there is a tendency that the resulting cured product has particularly excellent properties in terms of adhesion, connection reliability, insulation reliability and heat resistance. Based on the mass of the cured product, the content of the rubber component (A) in the cured product may be within the above range.
[0039] <(B) Cross-linking component having an epoxy group>
[0040] (B) The cross-linking component having an epoxy group is a component that forms a cross-linked polymer by cross-linking during the curing reaction. (B) The cross-linking component having an epoxy group is a component that is not equivalent to the rubber component (A). (B) The cross-linking component having an epoxy group is not particularly limited if it has an epoxy group in the molecule, and can be, for example, a conventional epoxy resin. The epoxy resin can be any of monofunctional, difunctional, or polyfunctional (trifunctional or more), and is not particularly limited, but from the perspective of more fully obtaining curability, a difunctional or polyfunctional epoxy resin can be used.
[0041] Examples of epoxy resins include bisphenol A type, bisphenol F type, phenol novolac type, naphthalene type, dicyclopentadiene type, cresol novolac type, and the like. From the viewpoints of low viscosity, dielectric properties, and heat resistance, as the crosslinking component (B) having an epoxy group, a naphthalene type or dicyclopentadiene type epoxy resin may be selected, or a dicyclopentadiene type epoxy resin may be selected. These epoxy resins may be used alone or in combination of two or more.
[0042] The combination of a rubber having a maleic anhydride group or a carboxyl group and a compound having an epoxy group (epoxy resin) tends to provide particularly excellent effects in terms of heat resistance, low moisture permeability, and adhesion of the cured product. If the heat resistance of the cured product is improved, for example, degradation of the cured product in a heating process such as nitrogen reflux can be suppressed.
[0043] The weight average molecular weight of the crosslinking component (B) having an epoxy group may be, for example, 200 to 2000, and is preferably 200 to 1000, more preferably 250 to 800, further preferably 300 to 550, and particularly preferably 350 to 450 from the viewpoint of the fluidity of the resin composition and the dielectric properties of the cured product.
[0044] The number average molecular weight of the crosslinking component (B) having an epoxy group may be, for example, 100 to 1000, and is preferably 150 to 500, more preferably 200 to 400, further preferably 250 to 350, and particularly preferably 250 to 300 from the viewpoint of the fluidity of the resin composition and the dielectric properties of the cured product.
[0045] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are values calculated in terms of standard polystyrene determined by gel permeation chromatography (GPC).
[0046] (B) The epoxy equivalent of the cross-linking component having an epoxy group may be, for example, 200 g / eq to 330 g / eq. From the viewpoint of the fluidity of the resin composition and the dielectric properties of the cured product, it may be 220 g / eq to 310 g / eq, 220 g / eq to 290 g / eq, 220 g / eq to 270 g / eq or 230 g / eq to 260 g / eq.
[0047] The curable resin composition may contain other crosslinking components other than the crosslinking component (B) having an epoxy group within a range that does not significantly impair the effects of the present disclosure. From the viewpoint of more fully reducing the dielectric loss tangent of the cured product, the content of the other crosslinking components is preferably less than 10 parts by mass relative to 100 parts by mass of the crosslinking component (B) having an epoxy group.
[0048] <(C) Ester hardener>
[0049] (C) The ester-based hardener is a compound that itself participates in the hardening reaction and can improve the heat resistance of the hardened material and reduce the dielectric loss tangent.
[0050] As ester hardeners, there are no particular restrictions. From the perspective of more fully obtaining the effect of improving heat resistance and reducing dielectric loss tangent, phenol esters, esters containing dicyclopentadiene structures, esters containing naphthalene structures, thiophenol esters, N-hydroxylamine esters, esters of heterocyclic hydroxyl compounds, etc., which have one or more highly reactive ester groups in one molecule, can be preferably used. As ester hardeners, compounds containing naphthalene structures can also be used. As ester hardeners, more specifically, for example, "Epiclon HPC8000-65T", "Epiclon HPC8000-L-65MT", "Epiclon HPC8150-60T", "Epiclon HPC8150-62T", "Epiclon HPC8150-65T" (all trade names manufactured by DIC Corporation) and the like can be cited. These may be used alone or in combination of two or more.
[0051] It is believed that the ester curing agent reacts with the crosslinking component (B) as shown in the following formula (I) during the curing reaction. It is believed that no hydroxyl group is generated in the reaction between the ester curing agent (C) and the crosslinking component (B), and even if a side reaction occurs, hydroxyl group is unlikely to be generated, resulting in a low dielectric loss tangent.
[0052] [Chemistry 1]
[0053]
[0054] In the formula, R 1 , R 2 and R 3 Each independently represents a monovalent organic group, and may be a monovalent organic group having an aromatic ring in that the effects of the present disclosure can be more fully obtained.
[0055] The curable resin composition may contain other curing agents other than the (C) ester curing agent within a range that does not significantly impair the effects of the present disclosure. From the viewpoint of more sufficiently reducing the dielectric loss tangent of the cured product, the content of the other curing agent is preferably less than 10 parts by mass relative to 100 parts by mass of the (C) ester curing agent.
[0056] In the curable resin composition, the total content of the (B) cross-linking component and the (C) ester curing agent is preferably 5% to 40% by mass, more preferably 10% to 35% by mass, and further preferably 15% to 30% by mass, based on the total amount of the (A) rubber component, the (B) cross-linking component, and the (C) ester curing agent. If the total content of the (B) cross-linking component and the (C) ester curing agent is 5% by mass or more, there is a tendency that more sufficient curing is easily obtained and the cured product has particularly excellent properties in terms of adhesion, connection reliability, insulation reliability, and heat resistance. If the total content of the (B) cross-linking component and the (C) ester curing agent is 40% by mass or less, there is a tendency that the rubber component and the cross-linking component are fully mixed, and there is a tendency that the cured product has more excellent properties in terms of dielectric properties.
[0057] In the curable resin composition, the content ratio of the crosslinking component (B) to the ester curing agent (C) is preferably in the range of 4:5 to 5:4, more preferably in the range of 4.5:5 to 5:4.5, in terms of the equivalent ratio of the epoxy group in the epoxy resin (B) to the ester bond in the ester curing agent (C). When the content ratio is within the above range, there is a tendency that more sufficient curing is easily obtained and the cured product has particularly excellent properties in terms of dielectric properties, adhesion, insulation reliability and heat resistance.
[0058] <(D) Hardening accelerator>
[0059] (D) The hardening accelerator is a compound that functions as a catalyst for the hardening reaction. (D) The hardening accelerator may also be a hardening accelerator selected from tertiary amines, imidazoles, organic acid metal salts, phosphorus compounds, Lewis acids, amine complex salts and phosphines. Among these, imidazoles can be used from the perspective of the storage stability, hardening properties and dielectric properties of the varnish of the curable resin composition. In the case where the rubber component (A) contains a rubber partially modified with maleic anhydride, an imidazole compatible therewith may also be selected. Imidazole may also be 1-benzyl-2-methylimidazole.
[0060] In the curable resin composition, the content of the (D) curing accelerator may be 0.1 to 10 parts by mass relative to the total amount of 100 parts by mass of the (A) rubber component, the (B) crosslinking component and the (C) ester curing agent. If the content of the (D) curing accelerator is 0.1 parts by mass or more, there is a tendency to easily obtain more sufficient curing. If the content of the (D) curing accelerator is 10 parts by mass or less, there is a tendency that particularly excellent effects can be obtained in terms of the storage stability of the varnish, film, etc. of the curable resin composition, the heat resistance of the cured product, and the dielectric properties of the cured product. From the above viewpoints, the content of the (D) curing accelerator may be 0.3 to 7 parts by mass, 0.3 to 5 parts by mass, 0.3 to 2 parts by mass, 0.3 to 1 part by mass, 0.5 to 5 parts by mass, 0.5 to 2 parts by mass, or 0.5 to 1 part by mass.
[0061] <(E) Filler>
[0062] When the curable resin composition contains (E) a filler, the coefficient of linear expansion (CTE) of the cured product can be reduced.
[0063] The filler (E) may be a filler having at least one group selected from the group consisting of a (meth)acryloyl group, a vinyl group, an epoxy group, and a phenylamino group. By having these groups, there is a tendency to have particularly excellent properties in terms of compatibility with the resin component at the filler interface, dispersibility of the filler, storage stability of the curable resin composition, linear expansion coefficient of the cured product, and adhesion of the cured product. Therefore, the curable resin composition can be more preferably used as an interlayer adhesive for a multilayer printed wiring board.
[0064] As the filler (E), from the viewpoint of linear expansion coefficient and adhesiveness, it is preferred that the filler contains at least one group selected from the group consisting of a (meth)acryloyl group, a vinyl group, an epoxy group and a phenylamino group, it is more preferred that the filler contains at least one group selected from the group consisting of a vinyl group, an epoxy group and a phenylamino group, and it is even more preferred that the filler contains an epoxy group.
[0065] As the filler (E), from the viewpoint of linear expansion coefficient and adhesion to low-polarity resin substrates, a filler having a vinyl group or an epoxy group is more preferred, and from the same viewpoint, a filler having an epoxy group is particularly preferred. As the low-polarity resin substrate, for example, a liquid crystal polymer can be cited.
[0066] (E) filler may be a filler to which surface treatment has been applied. The surface treated filler may be obtained by treating the surface of the filler with a surface treatment agent such as an organosilane compound. By treating the surface of the filler, there is a tendency to have particularly excellent properties in terms of compatibility with the resin component at the filler interface, dispersibility of the filler, storage stability of the curable resin composition, linear expansion coefficient of the cured product, and adhesion of the cured product. Therefore, by using a filler to which surface treatment has been applied as (E) filler, the curable resin composition may be more suitably used as an interlayer adhesive of a multilayer printed wiring board. As a surface treatment, surface modification may be applied.
[0067] As the surface-treated filler, from the viewpoint of linear expansion coefficient and adhesiveness, it is preferred to include a filler having at least one group selected from the group consisting of a (meth)acryloyl group, a vinyl group, an epoxy group and a phenylamino group, more preferably a filler having at least one group selected from the group consisting of a vinyl group, an epoxy group and a phenylamino group, and even more preferably a filler having an epoxy group.
[0068] As the surface treated filler, from the viewpoint of linear expansion coefficient and adhesion to low polarity resin substrate, a filler having a vinyl group or an epoxy group is further preferred, and from the same viewpoint, a filler having an epoxy group is particularly preferred. As the low polarity resin substrate, for example, a liquid crystal polymer can be cited.
[0069] When the surface treatment filler is used, the cured product of the curable resin composition tends to have further improved adhesion to materials constituting a printed wiring board, and in particular, tends to have further improved adhesion to substrates having a surface with little or no roughening. In conventional curable resin compositions, for example, it is difficult to improve adhesion to a liquid crystal polymer film without roughening, but the cured product of the curable resin composition containing the surface treatment filler tends to have good adhesion to a resin substrate with low polarity, such as a liquid crystal polymer film without roughening.
[0070] From the viewpoint of achieving both the fluidity of the curable resin composition and the reduction of the linear expansion coefficient of the cured product, the content of the filler (E) may be 30% to 75% by mass, 30% to 70% by mass, 40% to 70% by mass, or 50% to 70% by mass based on the total solid content of the curable resin composition. If the content of the filler (E) is within the above range, both the fluidity of the curable resin composition and the reduction of the linear expansion coefficient of the cured product can be achieved.
[0071] From the viewpoint of excellent dielectric properties, adhesion and film appearance of the cured product, the average particle size of the (E) filler may be 0.01 μm or more, 0.1 μm or more or 0.2 μm or more, and may be 5.0 μm or less, 4.0 μm or less, 3.0 μm or less, 1.0 μm or less or 0.8 μm or less. That is, the average particle size of the (E) filler is 0.01 μm to 5.0 μm, 0.1 μm to 4.0 μm, 0.2 μm to 3.0 μm, 0.2 μm to 1.0 μm or 0.2 μm to 0.8 μm. The average particle size of the (E) filler refers to the particle size with a cumulative frequency of 50% in the particle size distribution obtained by the laser diffraction / scattering method.
[0072] As (E) filler, inorganic fillers can also be used from the perspective of further reducing the linear expansion coefficient and improving the elastic coefficient. As inorganic fillers, for example, fillers containing at least one inorganic substance selected from the group consisting of silica, alumina, titanium dioxide, tantalum oxide, zirconium oxide, silicon nitride, gallium oxide, boron nitride, barium titanate, barium carbonate, magnesium carbonate, aluminum hydroxide, magnesium hydroxide, lead titanate, lead zirconate titanate, lanthanum zirconate titanate, spinel, mullite, cordierite, talc, aluminum titanate, zirconium oxide containing yttria, barium sulfate, barium silicate, calcium carbonate, calcium sulfate, zinc oxide and magnesium titanate can be listed. Inorganic fillers can be used alone or in combination of two or more. Among these, from the perspective of dispersibility and heat resistance of the cured product, the inorganic filler can be an inorganic filler containing any one of silica, alumina, titanium dioxide or boron nitride. From the perspective of dielectric properties, the inorganic filler can also be an inorganic filler containing silica.
[0073] As the (E) filler, an organic filler may also be used. The organic filler is generally in the form of particles and is dispersed in an organic solvent without being dissolved. In addition, the organic filler is not equivalent to the (A) rubber component. As the organic filler, fillers including liquid crystal polymers (LCP) and polytetrafluoroethylene (PTFE) may be listed. The organic filler may be used alone or in combination of two or more. In addition, the (E) filler may be a combination of one or more inorganic fillers and one or more organic fillers.
[0074] As filler (E), from the viewpoint of dispersibility and heat resistance, it can be an inorganic filler obtained by surface-treating silica, alumina, titanium dioxide or boron nitride, or an inorganic filler obtained by surface-treating silica, alumina or boron nitride. From the viewpoint of linear expansion coefficient and adhesion, filler (E) can be a surface-treated silica filler obtained by surface-treating silica.
[0075] As the surface treatment agent for the inorganic filler, organic silane compounds such as epoxy silane compounds, amino silane compounds, (meth)acrylic silane compounds and vinyl silane compounds may be used from the viewpoint of linear expansion coefficient and adhesiveness.
[0076] Examples of the organosilane compound include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-phenylaminopropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, vinyltriacetoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltriethoxysilane. Isopropoxysilane, allyltrimethoxysilane, diallyldimethylsilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltriethoxysilane, N-(1,3-dimethylbutylene)-3-aminopropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate and 3-isocyanatepropyltriethoxysilane.
[0077] <Other ingredients>
[0078] In addition to the above components, the curable resin composition may further contain an antioxidant, an anti-yellowing agent, an ultraviolet absorber, a visible light absorber, a colorant, a plasticizer, a stabilizer, a filler, a flame retardant, a leveling agent, etc. as needed within a range that does not significantly impair the effects of the present disclosure.
[0079] In particular, the curable resin composition may contain at least one anti-degradation agent selected from the group consisting of antioxidants, heat stabilizers, light stabilizers, and anti-hydrolysis agents. Antioxidants inhibit degradation caused by oxidation. In addition, antioxidants impart sufficient heat resistance at high temperatures to the cured product. Heat stabilizers impart stability at high temperatures to the cured product. Examples of light stabilizers include ultraviolet absorbers that prevent degradation caused by ultraviolet rays, light blockers that block light, and matting agents that have a matting function that receives light energy absorbed by organic materials and stabilizes organic materials. Anti-hydrolysis agents inhibit degradation caused by moisture. The anti-degradation agent may be at least one selected from the group consisting of antioxidants, heat stabilizers, and ultraviolet absorbers. As the anti-degradation agent, only one of the components exemplified above may be used, or two or more may be used in combination. In order to obtain a more excellent effect, two or more anti-degradation agents may be used in combination.
[0080] The curable resin composition can be prepared as a resin varnish in which the above-mentioned components are dissolved or dispersed in an organic solvent. The organic solvent is not particularly limited, and examples thereof include: aromatic hydrocarbons such as toluene, xylene, mesitylene, cumene, and p-cymene; cyclic ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone (MethylEthyl Ketone, MEK), methyl isobutyl ketone (Methyl Isobutyl Ketone, MIBK), cyclohexanone, and 4-hydroxy-4-methyl-2-pentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. From the viewpoint of solubility and boiling point, toluene or N,N-dimethylacetamide can also be used. These organic solvents may be used alone or in combination of two or more. The solid content (components other than the organic solvent) concentration in the resin varnish may be 20% by mass to 80% by mass.
[0081] The mixing and kneading of the resin varnish can be appropriately performed by combining a common disperser such as a stirrer, a pestle, a three-roll mill, or a ball mill.
[0082] [Curing film and laminated film]
[0083] The curable film of the present embodiment comprises the curable resin composition. The curable film can be easily manufactured, for example, by applying a resin varnish containing the curable resin composition to a substrate film and removing the solvent from the coating film. By the method, a laminated film including a substrate film and a curable film disposed on the substrate film can be obtained.
[0084] The solvent is removed from the coating on the substrate film by drying at a temperature at which the curable resin composition does not cure and under conditions where the solvent is fully volatilized. Specifically, the coating is usually dried by heating at 60°C to 180°C for 0.1 minutes to 90 minutes. The preferred residual volatile components of the resulting curable film are 10% by mass or less. If the residual volatile components are 10% by mass or less, it is easy to suppress the foaming caused by the volatilization of the solvent during assembly heating and the residual voids inside the cured product. In addition, it is easy to suppress the contamination of surrounding materials or components caused by the volatile components generated during heating.
[0085] The material of the substrate film is not particularly limited, and examples thereof include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate; polyolefins such as polyethylene and polypropylene; polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyether sulfide, polyether sulfone, polyether ketone, polyphenylene oxide, polyphenylene sulfide, polyarylate, polysulfone, and liquid crystal polymer. Among these, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polypropylene, polycarbonate, polyamide, polyimide, polyamideimide, polyphenylene oxide, polyphenylene sulfide, polyarylate, and polysulfone are preferred from the viewpoint of flexibility and toughness.
[0086] The thickness of the substrate film can be appropriately changed according to the target flexibility, and can be 3 μm to 250 μm. If it is usually 3 μm or more, the film strength is sufficient, and if it is 250 μm or less, sufficient flexibility can be obtained. From the above point of view, the thickness can be 5 μm to 200 μm or 7 μm to 150 μm. From the point of view of improving the peelability with the curable film, a substrate film subjected to a demolding treatment using a silicone compound, a fluorine-containing compound, etc. can also be used as needed.
[0087] If necessary, a protective film may be attached to the curable film to form a laminated film having a three-layer structure including a base film, a curable film, and a protective film.
[0088] The material of the protective film is not particularly limited, and examples thereof include polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefins such as polyethylene and polypropylene, etc. Among these, polyesters such as polyethylene terephthalate; and polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of flexibility and toughness. From the viewpoint of improving the peelability from the curable film, a protective film subjected to a release treatment using a silicone compound, a fluorine-containing compound, etc. may be used as needed.
[0089] The thickness of the protective film can be appropriately changed according to the target flexibility, and can be 10 μm to 250 μm. Generally, if the thickness is 10 μm or more, the film strength is sufficient, and if it is 250 μm or less, sufficient flexibility can be obtained. From the above point of view, the thickness can be 15 μm to 200 μm or 20 μm to 150 μm.
[0090] The thickness of the curable film after drying is not particularly limited, and is generally 5 μm to 1000 μm. If the thickness is 5 μm or more, the curable film or its cured product tends to easily obtain sufficient strength. If the thickness is 1000 μm or less, since sufficient drying can be performed, there is a tendency to easily reduce the amount of residual solvent in the curable film.
[0091] The laminated film can be easily stored by being wound into a roll, for example, or the laminated film can be stored by cutting the rolled film into a sheet of an appropriate size.
[0092] The curable resin composition, curable film and laminated film of this embodiment are suitable for forming a protective layer (cover layer) for covering a circuit in a printed wiring board and an interlayer adhesive in a multilayer printed wiring board, and are particularly suitable for forming a protective layer (cover layer).
[0093] [Printed wiring board]
[0094] The printed wiring board in this embodiment includes a laminate formed by a metal portion forming a circuit (conductor circuit) and a resin substrate as a constituent element. The printed wiring board can be manufactured, for example, using a metal-clad laminate and by existing known methods such as a subtractive method. The printed wiring board in this embodiment is generally referred to as a so-called flexible circuit board (Flexible Printed Circuit (Flexible Printed Circuit, FPC)), a flat cable, a circuit board for tape automated bonding (Tape Automated Bonding, TAB), etc., which is obtained by partially or fully covering the conductor circuit formed by the metal portion using a cover film or screen printing ink, etc. as needed.
[0095] The printed wiring board of this embodiment can be set as any laminated structure that can be used as a printed wiring board. For example, it can be set as a printed wiring board having a base material layer, an adhesive layer, a metal portion, and a protective layer.
[0096] Furthermore, if necessary, the printed wiring board may be a multilayer printed wiring board structure in which two or more printed wiring boards are stacked using an interlayer adhesive.
[0097] In the printed wiring board of the present embodiment, any base material conventionally used as a base material of a printed wiring board can be used as the base material layer.
[0098] In the printed wiring board of the present embodiment, as the substrate layer, any resin used as the substrate of the printed wiring board can be used. As the resin of the substrate layer, fluorine resins (PTFE etc.) such as polyester resin, polyamide resin, polyimide resin, polyamide-imide resin, epoxy resin, maleimide resin, liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resin, polytetrafluoroethylene (PTFE) etc. can be illustrated.
[0099] The curable resin composition of the present embodiment can be used for each adhesive layer, protective layer, and interlayer adhesive of a printed wiring board. In particular, if the curable resin composition of the present embodiment is used to form these layers, the materials constituting the printed wiring board, such as the substrate layer, the metal part, etc., have high adhesion, and the layer itself formed using the curable resin composition has excellent low dielectric properties. The cured product of the curable resin composition of the present embodiment also has excellent adhesion to low-polarity substrates such as liquid crystal polymers, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resins, and PTFE. Therefore, it is suitable as a curable resin composition used in a cover film, a laminate, a copper foil with a resin, and a bonding sheet. In addition, the curable resin composition of the present embodiment contains (A) a rubber component, so its cured product can have flexibility. Therefore, the curable resin composition of the present embodiment can be suitably used as a protective layer forming purpose and an interlayer adhesive of a flexible printed wiring board.
[0100] In the printed wiring board of the present embodiment, as metal part, it is not particularly limited, and from the viewpoint of wiring formation, it can be copper. As the material forming copper, it is not particularly limited, for example, the electrolytic copper foil and rolled copper foil used in copper-clad laminate and printed wiring board etc. can be used. As commercially available electrolytic copper foil, for example, F0-WS-18 (manufactured by Furukawa Electric Co., Ltd., trade name), NC-WS-20 (manufactured by Furukawa Electric Co., Ltd., trade name), YGP-12 (manufactured by Nippon Electrolysis Co., Ltd., trade name), GTS-18 (manufactured by Furukawa Electric Co., Ltd., trade name) and F2-WS-12 (manufactured by Furukawa Electric Co., Ltd., trade name), F2-WS-18 (manufactured by Furukawa Electric Co., Ltd., trade name) can be cited. As rolled copper foil, for example, TPC foil (manufactured by JX Metal Co., Ltd., trade name), HA foil (manufactured by JX Metal Co., Ltd., trade name), HA-V2 foil (manufactured by JX Metal Co., Ltd., trade name) and C1100R (manufactured by Sumitomo Mitsui Metal Mining and Copper Co., Ltd., trade name) can be cited. From the perspective of the adhesion of the cured product of the curable resin composition of the present embodiment, a copper foil to which a roughening treatment has been applied can also be used. From the perspective of folding resistance, a rolled copper foil can also be used. In addition, the metal portion may also have a roughened surface formed by a roughening treatment. In the case of using a copper foil to which a roughening treatment has been applied, from the perspective of transmission loss, the roughening treatment of the copper foil is preferably minimized, and it is preferred to use a finely roughened copper foil. As a finely roughened copper foil, for example, FV (FHG) -WS (FV-WS / FHG-WS, copper foil products, manufactured by Furukawa Electric Co., Ltd., trade name) and FZ-WS (copper foil products, manufactured by Furukawa Electric Co., Ltd., trade name) can be cited.
[0101] Above, the embodiment of the present disclosure is described in detail, but the present disclosure is not limited to the embodiment. For example, the curable resin composition can be used for the following purposes in addition to the composition or interlayer adhesive used for forming a protective layer (covering layer). That is, the curable resin composition can be used for the purposes such as the primer layer of the difficult-to-bond material, the bonding layer of the low-dielectric material with the bonding layer. As the coating method of the curable resin composition, it is not particularly limited, for example, a coating method such as a notch wheel coater, a rod coater, a die coater, dipping, and spin coating can be used. In addition, the curable film can be used for the purposes such as the resin layer of the copper foil with resin, and the low-dielectric telescopic substrate.
[0102] [Example]
[0103] The present disclosure will be described in more detail with reference to the following examples, but the present disclosure is not limited to these examples.
[0104] (Example 1 to Example 10 and Comparative Example 1 to Comparative Example 2)
[0105] <Preparation of Curable Resin Composition>
[0106] The materials shown in Table 1 were mixed at the solid content ratios (unit: parts by mass) shown in the table to prepare curable resin compositions. Toluene was added as a solvent to prepare the curable resin compositions so that the solid content was 25% by mass. Details of the materials are shown below.
[0107] (A) Rubber component
[0108] FG1924: Maleic anhydride modified styrene ethylene butylene styrene elastomer (Kraton Polymers Japan Co., Ltd., trade name "FG1924GT")
[0109] (B) Cross-linking component having epoxy group
[0110] HP7200L: dicyclopentadiene epoxy resin (manufactured by DIC Corporation, trade name "Epiclon HP-7200L", epoxy equivalent: 247 g / eq, number average molecular weight: 288, weight average molecular weight: 401)
[0111] HP7200: dicyclopentadiene epoxy resin (manufactured by DIC Corporation, trade name "EPICLON HP-7200", epoxy equivalent: 258 g / eq, number average molecular weight: 323, weight average molecular weight: 504)
[0112] HP7200H: dicyclopentadiene epoxy resin (manufactured by DIC Corporation, trade name "Epiclon HP-7200H", epoxy equivalent: 276 g / eq, number average molecular weight: 435, weight average molecular weight: 917)
[0113] HP7200HHH: dicyclopentadiene epoxy resin (manufactured by DIC Corporation, trade name "Epiclon HP-7200HHH", epoxy equivalent: 280 g / eq, number average molecular weight: 578, weight average molecular weight: 1774)
[0114] (C) Ester hardener
[0115] HPC8150-62T: ester hardener (manufactured by DIC Corporation, trade name "Epiclon HPC8150-62T", an active ester compound containing a naphthalene structure, a toluene solution with a solid content of 62% by mass)
[0116] (D) Hardening accelerator
[0117] 1B2MZ: 1-benzyl-2-methylimidazole (manufactured by Shikoku Chemical Industry Co., Ltd., trade name "1B2MZ")
[0118] <Production of Laminated Film>
[0119] A release-treated polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., trade name "Purex A3100", thickness 25 μm) was prepared as a substrate film. The curable resin composition was applied to the release-treated surface of the PET film using a knife coater (manufactured by Yasui Seiki Co., Ltd., trade name "SNC-350"). The coating was heated at 80° C. for 15 minutes in a dryer (manufactured by Futaba Scientific Co., Ltd., trade name "MSO-80TPS") to dry the coating to form a curable film with a thickness of 30 μm. On the formed curable film, a release-treated PET film identical to the substrate film was attached as a protective film with the release-treated surface being the curable film side, thereby obtaining a laminated film.
[0120] [Measurement of Adhesion]
[0121] The protective film of the laminated film obtained in the embodiment and the comparative example is peeled off, and an electrolytic copper foil (manufactured by Furukawa Electric Co., Ltd., trade name "F2-WS-18", thickness 18 μm) having a roughened surface with a surface roughness Rz of 1.8 μm is overlapped on the exposed curable film in a direction in which the roughened surface becomes the curable film side (hereinafter also referred to as "VLP-Cu foil"). In the above state, a vacuum pressurized laminator (manufactured by Nikko-Materials Co., Ltd., trade name "V130") is used to laminate the VLP-Cu foil to the curable film under the conditions of a pressure of 0.5 MPa, a temperature of 100°C, and a pressurization time of 60 seconds. Subsequently, the substrate film is peeled off, and the VLP-Cu foil is overlapped on the exposed curable film in a direction in which the roughened surface becomes the curable film side, and the VLP-Cu foil is laminated to the curable film under the above conditions. Then, the mixture was heated at 180° C. for 60 minutes in a dryer (manufactured by Futaba Scientific Co., Ltd., trade name “MSO-80TPS”) to obtain a laminate having the VLP-Cu foil, a cured film as a cured product of the curable film, and the VLP-Cu foil.
[0122] A sample for measuring peel strength of 100 mm in length and 5 mm in width was cut out from the obtained laminate. One of the VLP-Cu foil sides of the sample was fixed to a glass plate using an epoxy adhesive (manufactured by Huntsman Japan Co., Ltd., trade name "Araldite Rapid"). The following 90-degree peel test was performed: the other VLP-Cu foil and the cured film were grasped by a clamp, and the cured film was peeled off from the VLP-Cu foil fixed to the glass plate at a tensile speed of 50 mm / min using Autograph (manufactured by Shimadzu Corporation, trade name "EZ-LX"). The obtained peel strength measurement results are shown in Table 1. If the peel strength is 0.7 kN / m or more, it is qualified.
[0123] [Determination of relative dielectric constant (Dk) and dielectric loss tangent (Df)]
[0124] The hardened film is hardened by heating the laminated film obtained in the embodiment and the comparative example at 180°C for 60 minutes to harden the hardening film, thereby forming a hardened film. The substrate film and the protective film are removed from the hardened film, and the hardened film is cut into a size of 60 mm × 60 mm to obtain a test piece. Using the test piece, the relative dielectric constant (Dk) and the dielectric loss tangent (Df) are calculated by the split post dielectric resonator (Split post dielectric resonators, SPDR) method. The measuring instruments use vector network analyzers E8364B (manufactured by Keysight Technologies), CP531 (manufactured by Kanto Electronics Application Development Co., Ltd.) and CPMA-V2 (program) respectively, and the measurements are performed under the conditions of ambient temperature 25°C and frequency 10 GHz. The results are shown in Table 1.
[0125] [Table 1]
[0126]
Claims
1. A curable resin composition comprising (A) a rubber component, (B) a crosslinking component having an epoxy group, (C) an ester curing agent, and (D) a curing accelerator.
2. The curable resin composition according to claim 1, which is used to form a protective layer covering a circuit.
3. The curable resin composition according to claim 1, wherein The weight average molecular weight of the crosslinking component (B) having an epoxy group is 200 to 1,000.
4. The curable resin composition according to claim 1, wherein The content of the (D) curing accelerator is 0.1 to 10 parts by mass based on 100 parts by mass of the total amount of the (A) rubber component, the (B) crosslinking component having an epoxy group, and the (C) ester curing agent. 5 . A curable film comprising the curable resin composition according to claim 1 .
6. A laminated film comprising: A base film, and the curable film according to claim 5 provided on the base film.
